Correlation of Tumor Necrosis Factor Receptor-1 (TNFR1) with the Degree of Nephropathy in Diabetic Type 2 Patients - AL-Husseini, Wafaa Nouri Yassin; Mohamed, Kareem Galia (Medical Science Journal for Advance Research, 2024)
Background: Diabetes Mellitus (DM) is chronic metabolic disorder described by defects in action or secretion of insulin or both lead to hyperglycemia, the chronic diabetes hyperglycemia is related with dysfunction, failure and long-term damage of different organs. Type II diabetes mellitus (TIIDM) is a highly prevalent disease with a hereditary basis and the intervention of environmental risk factors, particularly bad lifestyle practices that lead to overweight and obesity. Diabetes mellitus is one of the world’s most serious public health issues. Diabetic patients have a high morbidity and mortality rate as a result of the development of various diabetic complications, including nephropathy, vasculopathy, cardiomyopathy, retinopathy, and neuropathy. Diabetic nephropathy is a complication of diabetes that affects approximately 40% of diabetic patients. Diabetic nephropathy, a primary cause of end-stage renal disease (ESRD), affects 30–40% of patients who require maintenance dialysis, putting an additional burden on healthcare systems. The present study was mainly aimed to the correlation TNF-receptor 1 , in serum as markers for primary detection of degree DN in a sample of Iraqi patients having type two diabetes mellitus (T2DM). Between August 2023 and January 2024, a grand total of 120 patients with type II DM were investigated. patients were selected from the Center of Diabetes and Endocrinology in Al-Sader Teaching Hospital in Najaf city were enrolled in this study. The patients were divided into three groups based on their albumin-to-creatinine ratio (ACR): normoalbuminuria, microalbuminuria, and macroalbuminuria. All participants underwent clinical evaluation along with a range of tests such as blood pressure, weight and height measurements, blood tests fasting blood sugar (FBS), glycated hemoglobin (HbA1c), serum urea and creatinine in addition to albumin and creatinine in urine. TNFR1 were measured by ELISA technique. The prevalence of microalbuminuria and macroalbuminuria was 63.29% and 11.10% respectively in the group of patients in this research. This implies that diabetic nephropathy is present in about 74.39% of the diabetic populations in this research. Conclusion: Based on the result of this study a significantly high concentrations of TNF receptor 1 were discovered in diabetic patients with macroalbuminuria and microalbuminuria compared to diabetic groups with normoalbuminurin. TNFR receptor 1 was found No correlating with the age,gender urine creatinine and HbA1c.